Photosensitizing nanoparticles and the modulation of ROS generation - Tada, Dayane B.; Baptista, Mauricio S. (Frontiers in Chemistry, 2015)
The association of PhotoSensitizer (PS) molecules with nanoparticles (NPs) forming photosensitizing NPs, has emerged as a therapeutic strategy to improve PS tumor targeting, to protect PS from deactivation reactions and to enhance both PS solubility and circulation time. Since association with NPs usually alters PS photophysical and photochemical properties, photosensitizing NPs are an important tool to modulate reactive oxygen species (ROS) generation. Depending on the design of the photosensitizing NP, i.e., type of PS, the NP material and the method applied for the construction of the photosensitizing NP, the deactivation routes of the excited state can be controlled, allowing the generation of either singlet oxygen or other ROS. Controlling the type of generated ROS is desirable not only in biomedical applications, as in Photodynamic Therapy where the type of ROS affects therapeutic efficiency, but also in other technological relevant fields like energy conversion, where the electron and energy transfer processes are necessary to increase the efficiency of photoconversion cells. The current review highlights some of the recent developments in the design of Photosensitizing NPs aimed at modulating the primary photochemical events after light absorption.